Aspartate aminotransferase and mortality in patients with ischemic heart disease - Ndrepepa, Gjin; Holdenrieder, Stefan; Cassese, Salvatore; Xhepa, Erion; Fusaro, Massimiliano; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Kastrati, Adnan (Nutrition Metabolism and Cardiovascular Diseases, 2020)
Background and aims: Evidence on the association between aspartate aminotransferase (AST) activity and mortality of patients with ischemic heart disease (IHD) is limited. We investigated whether there is an association between AST activity and mortality in IHD patients. Methods and results: The study included 6857 patients with coronary angiography-proven IHD and AST activity within the reference range. AST activity measurements were available in all patients. The primary outcome was 3-year cardiac mortality. Patients were categorized in groups according to the AST activity tertiles: a group with AST within the 1st tertile (AST < 17.0 U/L), a group with AST within the 2nd tertile (AST > 17–24.5 U/L) and a group with AST within the 3rd tertile (AST > 24.5 U/L). Cardiac death (n = 297) occurred in 109, 69 and 119 patients in the 1st to 3rd AST tertiles (Kaplan–Meier estimates of mortality: 5.3%, 3.6% and 5.9%; univariable hazard ratio [HR] = 1.75, 95% confidence interval [CI] 1.30–2.36, P < 0.001 for tertile 3 vs. 2; HR = 1.13 [0.87–1.46], P = 0.370 for tertile 3 vs. 1; and HR = 0.65 [0.48–0.87], P = 0.004 for tertile 2 vs. 1). The association between AST and cardiac mortality was U-shaped. AST values <15 U/L (HR = 1.118 [1.009–1.238]) and >23 U/L (HR = 1.029 [1.003–1.056]) were associated with higher cardiac mortality compared with the reference value (21 U/L). After adjustment, the association between AST and cardiac mortality was attenuated (P = 0.133) but remained non-linear (P = 0.047). Conclusions: In patients with IHD, AST activity was associated with the risk of cardiac mortality with a U-shaped relationship. After adjustment, the association between AST and mortality was attenuated.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Aspartate aminotransferase; Coronary artery disease; Mortality; Prognosis